Competitiveness of cassava-based ethanol production in Southern Africa: a case of Angola, Malawi, Mozambique, South Africa and Zambia - Kambewa, E.; Mudimu, G.D.; Jumbo, S.; Mahungu, N.M.; Tafadzwa, E.; Nyanzunda, T.E.; Whingwiri, E. (International Institute of Tropical Agriculture, 2010)
Whereas the global economy has from time immemorial depended on fossil fuels, technological innovations are steadily paving ways to relieve pressure from the dwindling resources and combat the environmental consequences that come along with oil extraction and use. Production and use of bio-fuels such as ethanol and bio-diesel are among such innovations that are attracting attention both in developed and developing economies. Although Africa is the largest producer of cassava on the globe, the competitiveness of cassava based ethanol production in Africa has not be been adequately examined. This paper presents results of a feasibility study conducted in Angola, South Africa, Malawi, Mozambique and Zambia on the competitiveness of cassava based ethanol production. The results show that, relative to maize and sugarcane, the use of cassava in ethanol production is competitive on: (1) feed stock availability, 2) low production costs, and 3) high ethanol yield. Cassava has high yield potential of 6 – 40mt/ha compared to maize which yields about 1-3.5mt/ha. Hence less land would be required to grow the crop for ethanol production. Cassava production costs are low compared to sugarcane that requires huge (irrigation) infrastructure. Cassava yields up to16,000l ethanol per hectare compared to maize that yields about 800l/ha and sugarcane that yields about 7200l/ha. However, the study notes that conflict of use between food security needs and bio-fuel production need further understanding. The paper concludes that with large scale investment in cassava production, more research on high yielding cassava varieties and an enabling policy and institutional support, SADC countries would be able to venture into large scale cassava based ethanol production.